1995
DOI: 10.1002/bjs.1800820310
|View full text |Cite
|
Sign up to set email alerts
|

Faecal occult blood testing and colonoscopy in the surveillance of subjects at high risk of colorectal neoplasia

Abstract: Colonoscopy is the established method of surveillance of subjects at high risk of developing colorectal neoplasia but the procedure is expensive, time consuming and occasionally hazardous. Faecal occult blood tests can be prepared at home and are cheap, simple and safe. Hemeselect is an immunological faecal occult blood test that is more sensitive for colorectal cancer than Haemoccult. The aim of this study was to determine the sensitivity of the Hemeselect test for asymptomatic colorectal neoplasia in subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…A recent study14 involving a similarly high risk group as the present study demonstrated a positivity rate of 20% for HemeSELECT in 808 individuals; sensitivity for CRC and adenomas â©Ÿ1 cm was 70% and 44%, respectively, values similar to those obtained for calprotectin. A subset of 417 of the 808 persons also completed Hemoccult-II tests with sensitivities of 33% and 18%.…”
Section: Discussionsupporting
confidence: 87%
“…A recent study14 involving a similarly high risk group as the present study demonstrated a positivity rate of 20% for HemeSELECT in 808 individuals; sensitivity for CRC and adenomas â©Ÿ1 cm was 70% and 44%, respectively, values similar to those obtained for calprotectin. A subset of 417 of the 808 persons also completed Hemoccult-II tests with sensitivities of 33% and 18%.…”
Section: Discussionsupporting
confidence: 87%
“…A detection rate of 45% -81% has been reported for symptomatic cancers [21]. Immunological tests, specific for human haemoglobin, have been shown to be more sensitive for symptomatic colorectal cancer than guaiac-based tests [21,22] and there is some evidence to show that they are more sensitive as a screening method for the asymptomatic population as well [20]. However, the improvement in sensitivity is reached at the expense of specificity.…”
Section: Discussionmentioning
confidence: 95%
“…The studies that attempted to reduce verification bias are listed in Table 2. [51][52][53][54][55][56][57][58][59][60] These 10 studies included 185 subjects with colorectal cancer and 31,804 controls. Seven studies reduced verification bias by performing colonoscopy on all of the potential subjects 51,54-56,58-60 while 3 studies used longitudinal follow-up for at least 2 years.…”
Section: Included Studiesmentioning
confidence: 99%